2014
DOI: 10.1055/s-0034-1390084
|View full text |Cite
|
Sign up to set email alerts
|

Lesion-Related Carotid Angioplasty and Stenting with Closed-Cell Design without Embolic Protection Devices in High-Risk Elderly Patients—Can This Concept Work Out? A Single Center Experience Focusing on Stent Design

Abstract: Approximately 200,000 patients per year suffer from ischemic insult in Germany. Of those, approximately 30,000 originate from carotid stenosis. 1 Carotid artery stenting (CAS) has emerged as an alternative revascularization technique for extracranial carotid stenotic disease. 2 Nevertheless, one of the limitations of CAS is the potential for embolic stroke caused by plaque dislodgement of atheromatous material. 2 AbstractTo compare the performance differences of three carotid artery stents in high-risk elderly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…We conducted a systematic literature review without meta-analysis per Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines [8]. Nineteen studies were identified that discussed perioperative risk in the context of relevant anatomy [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] (Table 1) in addition to fourteen studies [28][29][30][31][32][33][34][35][36][37][38][39][40][41] (Table 2) and fifteen case reports/series [42][43][44][45][46][47][48][49][50][51][52][53][54]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We conducted a systematic literature review without meta-analysis per Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines [8]. Nineteen studies were identified that discussed perioperative risk in the context of relevant anatomy [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] (Table 1) in addition to fourteen studies [28][29][30][31][32][33][34][35][36][37][38][39][40][41] (Table 2) and fifteen case reports/series [42][43][44][45][46][47][48][49][50][51][52][53][54]…”
Section: Resultsmentioning
confidence: 99%
“…The predominant feared risk in CAS is AIS or TIA [62]. Available literature by way of retrospective case series and reports describes a variety of techniques to safely account for anatomy including unfavorable great vessel variants and angulations [28][29][30][31][32][33][34][35][36]38,39,41], near-total ICA stenosis [33,36,40], tortuosity [28,34,35,37,39], and vulnerable plaque morphology [38] in the context of carotid intervention. Modalities range from anchoring techniques [28], the use of dedicated guide catheters [55], and alternative access sites [30].…”
Section: Techniques For Hostile Anatomymentioning
confidence: 99%
See 1 more Smart Citation
“…There are pros [25,26,27,28] and cons [29,30] of using EPD in CAS. Proponents advocate EPD use because of its ability to eliminate emboli detected by transcranial Doppler sonography [31].…”
Section: Discussionmentioning
confidence: 99%